Alternative method for preparation of Au/TiO2 with precise Au0/Auδ+. Issue 7 (1st October 2015) - Du, Mingming; Huang, Jiale; Jing, Xiaolian; Sun, Daohua; Li, Qingbiao
Abstract: BACKGROUND: Au valence for Au catalysts has been considered a vital parameter for catalytic activity towards CO oxidation. However, there is no effective method to prepare precise Au 0 /Au δ+ molar ratios with the same Au nanoparticles (NPs) sizes. RESULTS: A series of Au/TiO2 catalysts with tuneable Au 0 /Au δ+ molar ratios were prepared by the combination of a biosynthesis method and a deposition–precipitation (DP) method, and characterized by XPS, TEM, DRUV‐Vis techniques. First, biosynthesized metallic Au NPs were immobilized onto TiO2 supports to obtain Au/TiO2 catalysts with different Au loadings but with the same sized Au NPs. And then positively ionized Au species were supported onto the above Au/TiO2 catalysts by a DP method. The metallic Au and positively ionized Au species could be totally supported on the support. Therefore, the Au 0 /Au δ+ molar ratios could be controlled exactly. Compared with Au/TiO2 catalysts with metallic and positively ionized Au species alone, the catalyst Au/TiO2 ‐1:1 showed the best initial catalytic activity, suggesting enhanced catalytic performance due to the coexistence of Au 0 and Au δ+ . CONCLUSION: This study verifies that Au/TiO2 catalysts with accurate Au 0 /Au δ+ molar ratios can be prepared by a combination of biosynthesis and a DP method. © 2015 Society of Chemical Industry